Effect of halo-type frontal cockpit protection on overtaking - Rosalie, Simon; Malone, J. (British Medical Journal Publishing Group, 2018)
© © BMJ Publishing Group Limited 2018. In 2018, the Fédération Internationale de l'Automobile introduced the halo frontal cockpit protection system into Formula 1. While extensive testing was conducted to confirm that the halo protects the driver from contact, the halo's effect on the driver during overtaking was not tested prior to its introduction. Here, we describe the effect of a halo-type structure on the neck muscle activity of one of the authors, a national-level amateur racing driver, during on-track simulations designed to practise overtaking. We found that the halo-type structure caused an increase in the rates of fatigue and workloads of sternocleidomastoid and cervical erector spinae. The results suggest that the driver adopted a forward and right laterally flexed head position, presumably to clear the central pillar from his visible field. This has the potential to increase compressive loading of the cervical spine and affect the ability to use visual cues during steering manoeuvres.